TRANSFORMING ENGLISH LANGUAGE EDUCATION IN UNIVERSITIES WITH DEEP LEARNING TECHNOLOGY - Dina Amaliyah Mushthoza (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
The integration of deep learning technology into English language education at universities has revolutionized the teaching and learning process. This article explores how deep learning enhances language acquisition by providing personalized learning experiences, automated assessments, and real-time feedback. Deep learning models, such as Natural Language Processing (NLP) and neural networks, contribute significantly to improving students' listening, speaking, reading, and writing skills. Moreover, adaptive learning systems powered by artificial intelligence enable a more interactive and engaging educational environment. Despite its numerous advantages, challenges such as data privacy, implementation costs, and the need for teacher training must be addressed. This study highlights the potential of deep learning technology in reshaping English language education and suggests strategies for its effective integration in higher education institutions.